History and Main Trends in the Development of Copyright - BONDARENKO, Natalia Grigoryevna; ALLALYEV, Ruslan Muradovich; SMIRNOV, Mikhail Guramovich; DUDCHENKO, Ann V.; STRIZHOVA, Ekaterina Valentinovna (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The article defines the history, development trends and some problematic provisions of copyright law. The relevance of the study is caused by the tendency to tighten copyright legislation. The purpose of the study is to explore the genesis of the institute of copyright and its modern state. Among the objectives set to achieve this objective there is identifying the causes and features of the legal regulation of authorship in different countries, analyzing the activities of global organizations that control the main international agreements in the area under study, identifying the main problems of the sphere, explaining their causes and offering a solution. The study provides various scientific perspectives on legal instruments for regulating the sphere. The domestic, foreign and international regulatory framework for creative results is analyzed. The reasons, origins of this institution and the prospects for further development are raised. The nature of the institution of copyright and the comparison of its development in different countries are identified. The essential conditions for the appearance of copyright in a given country are indicated. As a result of the study, the overall status of the studied area is summarized. The results of the study of different views on the mentioned problems are presented, and solutions to address the scientific and social interests are proposed. The scientific novelty and significance of this study are that the copyright institute is considered in the article as unique in nature and originally English phenomenon served to the creation of an autonomous world legislative network dictating further conditions for the participating countries.